Dialogues: the shaping of biotechnology in Southern Africa - Omamo, Steven Were; von Grebmer, Klaus (International Food Policy Research Institute, 2005)
IFPRI and FANRPAN outlined and managed a highly participatory process involving high-level policymakers, senior representatives of a range of stakeholder agencies, and respected scientific leaders, who came together for an integrated series of roundtable discussions. The initiative is distinctive for having an explicitly process-based perspective in a framework involving many stakeholders.The first of three policy dialogues took place in April 2003 in Johannesburg, South Africa. A subsequent dialogue took place in Harare, September 20–21, 2004; a third is planned for 2005. In selecting topics for the first dialogue, IFPRI and FANRPAN identified five areas in which governments are required to make new and unfamiliar choices in order to regulate agricultural biotechnologies: intellectual property rights, biosafety, trade, food safety and consumer choice, and public research.